Analysis on Implementation Effect of Groundwater Over-exploitation Comprehensive Control Water Conservancy Project—Taking Linzhang County as an Example. Issue 2 (September 2019) - Wang, Danyang; Zhang, Jing; Zhao, Jinyong; Fu, Yicheng; Zhao, Xinkai; Gong, Shaopeng
Abstract: In order to effectively solve the problem of over-exploitation of groundwater in Hebei Province and achieve the balance of groundwater recovery, Hebei Province began to conduct pilot research on comprehensive management of groundwater over-exploitation in 2014. Taking Linyi County in the south of Hebei Province as an example, this paper studies the effect of pressure extraction on groundwater over-exploitation comprehensive treatment of water conservancy projects in 2015, analyzes and summarizes the experience, deficiencies and improvement measures of groundwater pressure mining work, in order to follow the groundwater pressure mining work. Provide guidance for reference. The results show that: Linyi County's 2015 water conservancy project achieved a pressure recovery capacity of 4.02 million m 3, and the water-saving pressure mining effect was remarkable. Among them, the sprinkler irrigation water-saving facilities have an average water saving capacity of 105 m 3 /mu, and the water-saving efficiency is obvious. In addition, the next stage of work should pay attention to the study of water-saving measures based on water-saving management and regional agriculture represented by crop planting structure adjustment. Irrigation pattern, implementation of field engineering work, to form a regional scale, intensive water-saving irrigation pattern, promote the promotion and application of groundwater over-exploitation comprehensive treatment in Hebei Province.